Richard V. Teschner, Garland D. Bills, Jerry R. Craddock, Spanish and English of United States Hispanos. A critical, annotated, linguistic bibliography. Center for Applied Linguistics, Arlington, 1975; 352 pp. - Moreno de Alba, José G. (El Colegio de México, 1978)
Se reseñó el libro: Spanish and English of United States Hispanos. A critical, annotated, linguistic bibliography.